Global Problems on Nash Functions. - Coste, Michel; Ruiz, Jesús M. (Revista Matemática Complutense, 2004)
This is a survey on the history of and the solutions to the basic global problems on Nash functions, which have been only recently solved, namely: separation, extension, global equations, Artin-Mazur description and idempotency, also noetherianness. We discuss all of them in the various possible contexts, from manifolds over the reals to real spectra of arbitrary commutative rings.